2014
DOI: 10.1038/ncomms4550
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis overrides oxygen deprivation to maintain mitochondrial function and cell survival

Abstract: Sustained cellular function and viability of high-energy demanding post-mitotic cells rely on the continuous supply of ATP. The utilization of mitochondrial oxidative phosphorylation for efficient ATP generation is a function of oxygen levels. As such, oxygen deprivation, in physiological or pathological settings, has profound effects on cell metabolism and survival. Here we show that mild extracellular acidosis, a physiological consequence of anaerobic metabolism, can reprogramme the mitochondrial metabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
142
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 69 publications
12
142
2
1
Order By: Relevance
“…Therefore, APC-induced autophagy may target defective mitochondria and thereby render neuronal cells resistant to reperfusional injury. A recent study showed that low pH modulates mitochondrial shapes and sustains mitochondrial function and cell survival in hypoxia 11 . Together with our results, it appears that acidosis not only helps to remodel the healthy mitochondria but also to remove the defective ones by mitophagy.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, APC-induced autophagy may target defective mitochondria and thereby render neuronal cells resistant to reperfusional injury. A recent study showed that low pH modulates mitochondrial shapes and sustains mitochondrial function and cell survival in hypoxia 11 . Together with our results, it appears that acidosis not only helps to remodel the healthy mitochondria but also to remove the defective ones by mitophagy.…”
Section: Resultssupporting
confidence: 87%
“…ASIC1/ASIC1α (acid-sensing [proton-gated] ion channel 1), the primary proton sensor in the nervous system, is localized in mitochondria and decreases mitochondrial membrane potential upon oxidative stress 10 . A more recent study showed that acidosis can maintain mitochondrial functions against hypoxia in neurons 11 . These studies highlight the possibility that acidosis targets mitochondrial function to protect the brain from ischemic injury.…”
Section: Introductionmentioning
confidence: 99%
“…While the late-gestation fetus has adaptive mechanisms to survive acute hypoxia/acidosis during parturition (50), less is known about the fetal response to chronic acidosis. Mild acidosis has been shown to reprogram mitochondrial metabolism by increasing respiratory efficiency to preserve ATP production during cellular stress (51), and it is likely that similar adaptations occur in Mpc1-deficient tissues. Our finding that 75 of 86 metabolites significantly regulated in both brain and liver of Mpc1 KI/KI embryos were regulated in the same direction suggests that the metabolic effects of MPC deficiency are largely conserved across tissues but that some responses are tissue specific.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, SAL has an inhibitory effect on oxidative phosphorylation and it is generally considered an inhibitor of mitochondrial function [61, 62], causing a very fast acidification of the mitochondrial matrix. Cell survival under acidosis was reported in post-mitotic cells to be mediated by a homeostatic adaptive response leading to increased mitochondrial function, including maximal respiratory capacity [63]. Interestingly, we observed that acid-adapted HCT116 cells show a higher maximal respiratory capacity as compared to cells cultured at physiological pH (Pellegrini et al, unpublished data) and it is conceivable to hypothesize that SAL-mediated inhibition of mitochondrial function may contribute to increase the sensitivity of cancer cells under acidosis.…”
Section: Discussionmentioning
confidence: 99%